KEBERLANJUTAN BELAJAR MEMBACA SISWA SEKOLAH DASAR DI KECAMATAN JEROWARU - Syahredi, Hardiman; Nahdi, Khirjan; Deni Siregar, Muhammad; Alfian Hadi, Yul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the sustainability of reading learning of elementary school students in Jerowaru District outside school hours, by examining the role of teachers, and the form of parental support for reading activities at home. The urgency of this research is based on the importance of building the sustainability of reading habits in students amid the tendency to use time after learning activities in schools which are more widely used for play activities and the use of digital devices. The novelty of this research lies in the approach that links three integrated elements, namely, student reading activities, teacher direction and parental support, as a unit of the sustainability process of student reading learning. The method used is a qualitative descriptive approach implemented in two basic education units in East Lombok. The research informants consisted of two teachers, ten students, and ten parents or guardians of students. Data was collected through interviews, observations, and documentation, then analyzed using data condensation, data presentation, conclusion drawing and verification techniques. The results of the study show that the sustainability of reading learning at home has not been running optimally, even though teachers have given reading assignments and directions in the form of homework, and parents have provided assistance, motivation, and facilitation even though it has not been consistent. It can be concluded that the sustainability of students' learning to read after school hours has not run optimally because reading activities at home have not become a habit that is embedded in students.